WHAT IS THE ROLE OF CUSTOMER BEHAVIOR FOR ELECTRONIC E-COMMERCE AND MODERN MARKET VISIT INTENTION ? - Agus Purwanto (Journal of Information Systems and Management (JISMA), 2022)
- The aim tis research is to investigate the correlation of customer behaviour, electronic e-commerce and market visit intenrtion. This type of research is included in quantitative research. Respondents used in answering questions in the study were 300 visitors to the modern market which were determined by the simple random sampling method. Meanwhile, to obtain data, it was done by distributing online questionnaires to respondents who were used as research objects. The analytical tool used in this research is Structure Equation Models (SEM) with the Partial Least Square (PLS) approach with the smartPLS 3.0 software tool . This research method uses a survey, where questionnaires are distributed to obtain answers to research questions. Data obtained through online questionnaires distributed through social media and Structure Equation Model (SEM) analysis with Partial Least Square (PLS) approach with software data processing tools. SmartPLS 3.0. The results show that Customer Behavior has a significant effect on E -Commerce, Customer Behavior has a significant effect on Modern Market visit intention, E-Commerce has a significant effect on Modern Market visit intention. Effective and efficient in conducting transactions is highly desired by consumers today. When going to buy a product, you don't have to go directly to the mall or shopping place but can go through an online application. Various shopping options on e-commerce are very popular, especially by millennials, because they are considered practical, effective and efficient